Job attitudes.[article]. - Judge, Timothy A.
Job attitudes research is arguably the most venerable and popular topic in organizational psychology. This article surveys the field as it has been constituted in the past several years. Definitional issues are addressed first, in an attempt to clarify the nature, scope, and structure of job attitudes has been an issue of debate, and recent research using within-persons designs has done much to inform this discussion. Recent research has also begun to reformulate the question of dispositional or situational influences on employee attitudes by addressing how these factors might work together to influence attitudes. Finally, there has also been a continual growth in research investigating how employee attitudes are related to a variety of behaviors at both the individual and aggregated level of analysis. - (from the authors)
Keywords: Kammeyer-Mueller, John D; Attitudes; Job attitudes; Job satisfaction; Mood; Emotions; Personality; Performance